The Effect Of Problem Based Learning Model With Mind Mapping Technique On Biology Learning Achivement - Yuli Arahmat; Suratno Suratno; Bevo Wahono (Pancaran Pendidikan, 2017)
Indonesia is a country that continuous to improve and develop its education system. The development of learners abilities that are needed nowadays not only develop cognitive ability alone will be much more than that, it needs an attitude awareness in the learning process. The purpose of this research is to know the effect of the problem-based learning model with mind mapping technique. Biological material used in this study is the subject of the virus. The first research result is learning the model of learning for student cognitive learning result. Based on the results of ANAKOVA analysis shows the significance level less than 0.05, then this shows the significant effect of the difference between the learning class and control class on the learning achievement of cognitive aspects. The second research result is to test the difference of learning the result of the affective domain between problem-based learning model with mind mapping technique and conventional learning model. The result of learning effective sphere which is assessed based on direct observation covering 5 indicators namely; Discipline, daring opinion, responsibility, cooperation and tolerance, Based on the analysis One sample t-test 2 indicator shows the level of significance less than 0.05, then this shows there are significant differences 2 indicators of effective learning achievement. 2 indicators are daring opinion and cooperation.